Remotely piloted aircraft systems and journalism: opportunities and challenges of drones in news gathering - Goldberg, D; Corcoran, M; Picard, R (2013)
This report summarizes issues raised by journalists, policy and legal specialists in the challenges posed by the use of unmanned aircraft in news gathering. It includes research to help news organisations evaluate the potential for use of these tools, to understand the broader context and issues surrounding their use, to consider how they might be used, and to assess the desirability of their use.